Crustal deformation and dynamics of the south-eastern tibetan plateau from stress fields and geodesy - Wang, Kaiying; Feng, Xiangdong (Frontiers in Earth Science, 2022)
South-eastern Tibet rotates clockwise around the eastern Himalayan syntaxis due to the eastward extrusion of the eastern Tibetan lithosphere and it attracts much attention as a window for studying the dynamics of continental collision between India and Eurasia. Competing geodynamic models to describe the deformation of the eastern Tibet have been the debating subject and the dynamic processes responsible for plateau evolution remain poorly understood, partly because the mechanical state at depth and its relationship with surficial deformation are unclear. In this context, a continuous east–west oriented tensional zone was identified at the south-eastern edge of the Tibetan Plateau based on seismogenic stress field and global positioning system data. The profiles of surficial velocity field reveal a relatively speedy motion belt parallel to the Xianshuihe Fault extending from north to south in the rotating region east of the tensional zone. Segmented features of the profiles around the extensional zone indicate its close relation with two major flow channels delineated from magnetotelluric images. Therefore, the deformation at the south-eastern edge of the Tibetan Plateau is mechanically coupled within the crustal depth. We propose that crustal material structure with flow channels and lateral variations in boundary conditions play a significant role in the geodynamics and lithospheric deformation in south-eastern Tibet.